2001
DOI: 10.1159/000047830
|View full text |Cite
|
Sign up to set email alerts
|

Development of Human Fetal Pancreas after Transplantation into SCID Mice

Abstract: Only a small component of human fetal pancreas consists of β cells, and yet this tissue is capable of normalizing the blood glucose levels of diabetic recipients when transplanted. The time taken to achieve this goal is several months, during which time the tissue proliferates and eventually differentiates into β cells. The dynamics of β cell development have not been described previously. We transplanted human fetal pancreas beneath the renal capsule of immunodeficient mice and analysed the grafts for a perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…To examine the immunogenicity of first-trimester human fetal pancreas, a humanized mouse model was established. We determined that the optimal number of human PBMCs to achieve engraftment in NOD/SCID mice was 5 ϫ 10 7 and that second-trimester human fetal pancreas, which is known to be immunogenic, was rejected after 3 weeks when transplanted in this model (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the immunogenicity of first-trimester human fetal pancreas, a humanized mouse model was established. We determined that the optimal number of human PBMCs to achieve engraftment in NOD/SCID mice was 5 ϫ 10 7 and that second-trimester human fetal pancreas, which is known to be immunogenic, was rejected after 3 weeks when transplanted in this model (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, after transplantation into diabetic immunoincompetent rodents, the tissue consistently differentiates into a functionally mature graft (2-6) containing ␤-cells and other endocrine cells (7) and is able to normalize blood glucose levels (BGLs) in diabetic rodents (2,3,5,6). Another advantage of transplanting fetal tissue is its possible immune privileged status, as has been demonstrated for other fetal tissue transplants (8 -11).…”
mentioning
confidence: 92%
“…Portal vein, liver (Pepper et al, 2013;Carlsson et al, 2001), spleen (Gray, 1990), omentum, pancreas, muscle, gastric sub mucosa, subcutaneous, genitourinary tract, anterior eye chamber, thymus and testis are the suggested sites for animal islet transplantation (Cantarelli and Piemonti, 2011;Rajab, 2010). Renal sub capsular space can provide a better condition for transplanted islet cells (Mellgren et al, 1986;Si et al, 2001;Hawthorne et al, 2011) and it is the most widely used site in rodents (Pepper et al, 2013). Also, in human it was reported that kidney, liver, muscle, and omentum are respectively the best sites for islet transplantation (Kim et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of Viability With Fluorescent Dyes collagenase in the two preparations was 3.15 and 3. 26 Viability of ICCs was tested using the fluorescent Wunsch U/mg, respectively. dyes, carboxyfluorescein diacetate (6-CFDA) and pro-The buffer used to dissolve collagenase was Dulbecpidium iodide (PI).…”
Section: Methodsmentioning
confidence: 99%